2018
DOI: 10.1097/aog.0000000000002613
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use and Survival Associated With Fertility-Sparing Trachelectomy for Young Women With Early-Stage Cervical Cancer

Abstract: Use of trachelectomy for early-stage cervical cancer has increased in the United States, particularly among women younger than 30 years of age. Within this population, survival is similar for trachelectomy and hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Although performance of trachelectomy remained uncommon, our study showed a gradual increase in the utilization of trachelectomy for reproductive-aged women with stage IB1 cervical cancer with tumors larger than 2 cm in the United States. Our results partly support the recent study using the National Cancer Database that demonstrated a significant increase in the utilization of fertility-sparing trachelectomy for women aged younger than 30 years with early-stage cervical cancer in the United States [ 6 ]. However, population-based statistics specific to stage IB1 cervical cancer with tumor size larger than 2 cm have not been examined previously.…”
supporting
confidence: 89%
“…Although performance of trachelectomy remained uncommon, our study showed a gradual increase in the utilization of trachelectomy for reproductive-aged women with stage IB1 cervical cancer with tumors larger than 2 cm in the United States. Our results partly support the recent study using the National Cancer Database that demonstrated a significant increase in the utilization of fertility-sparing trachelectomy for women aged younger than 30 years with early-stage cervical cancer in the United States [ 6 ]. However, population-based statistics specific to stage IB1 cervical cancer with tumor size larger than 2 cm have not been examined previously.…”
supporting
confidence: 89%
“…8 This increase was most pronounced in women <30 years of age. 5 Our study demonstrates that the majority of these procedures are now performed with a minimally invasive approach, particularly with use of the robotic platform. This increased use of MIS for trachelectomy parallels the trends observed for radical hysterectomy for early-stage cervical cancer in the United States.…”
Section: Commentsmentioning
confidence: 81%
“…The following abstracted data variables were categorized based on a previous study. 5 Demographic information of interest included age (in years), race/ ethnicity (white, black, Hispanic, other, or unknown), year of diagnosis, insurance type (private, Medicare, Medicaid, uninsured, other government or unknown), median household income (<$38,000, $38,000e47,999, $48,000e62,999, $63,000), education (measured as percentage of adults in the patient's zip code who did not graduate from high school and grouped as 21%, 13%e20%, 7.0%e12.9%, <7%), and urbanerural location (metropolitan, urban, rural, or unknown).…”
Section: Clinical Informationmentioning
confidence: 99%
See 2 more Smart Citations